Pertanggungjawaban Sosial Islam Pada Institusi Bisnis Islam - Nina Wiyandari; Sartini Wardiwiyono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to identify how an Islamic business institution implement their Islamic corporate social responsibility. It utilises qualitative research based on a case study. A large supermarket in Yogyakarta that is owned by a faithful Muslim businesswoman was selected as the object of the study. Primary data related to CSR activities, policies and initiatives were collected through interview and observation. The interviews involved 16 informants, who were employees, customers, local community member and CSR person in charge in the company. Qualitative data analysis) were conducted to achieve the research objective. A triangulation of data collection methods and sources were also applied to test the quality of the data. This study reveals that the company has implemented various kinds of responsibilities to employees, consumers, society and the environment. It had also implemented various forms of corporate social responsibility in Islam to all stakeholders. For the CSR distribution to the community, it should be given fairly to people in need so as not to cause jealousy in the surrounding community. This study contribute to the upward literature on Islamic CSR and could provide insight for Muslim business practitionaires how to address CSR in their daily operation. Keywords: CSR, Sustainability, Islam